69 Exploring learners' perspectives of a pediatric palliative care tele-mentoring and education program (project ECHO) in a resource-limited setting. (19th August 2020) - Evans, Emily; Doherty, Megan; Modanloo, Shokoufeh; Rowe, Jennifer; Newhook, Dennis; Archibald, Doug
Abstract: Introduction/Background: More than 98% of children who need palliative care live in low- or middle-income countries where access to palliative care is extremely limited. A lack of palliative care education for health care providers has been identified as a significant barrier to improving access to palliative care. Project ECHO (Extension of Community Healthcare Outcomes) is an online tele-mentoring educational platform developed to improve access to specialist care in these underserved areas. From 2018 to 2019, we piloted a one-year Project ECHO program which provided pediatric palliative care training for healthcare professionals mainly within India and surrounding South Asian countries. Objectives: The objective of this study was to explore the learning experiences of participants in a Project ECHO on pediatric palliative care in South Asia and explore considerations to improve ECHO to cater to the unique learning needs and challenges for healthcare professionals in resource-limited settings. Design/Methods: We implemented a one-year Project ECHO targeting healthcare providers in South Asia, which consisted of 24 bi-weekly 90-minute sessions. Learners who attended at least 20% (5 sessions) were invited to participate in focus groups. Focus groups were designed to explore participants' experiences and the perceived strengths and weaknesses of the program. Recordings of the focus group sessions were transcribed, coded and independently verified. The codes were then arranged into overarching themes. Results: Seventeen individuals from India and Bangladesh participated in four focus groups at the end of ECHO PPC. Following coding and analysis, two major themes and seven sub-themes were identified. The themes included: (1) Benefits of participation in ECHO PPC (creation of a community of practice; opportunity to exchange cultures, ideas and experiences; supportive role of the facilitator and peers; increased relevant knowledge and skills; and access to additional learning resources) and (2) Barriers to participation (difficulties with time and practice schedule management; and language and sociocultural factors). Conclusion: Healthcare professionals in resource-limited settings benefit from project ECHO through the creation of a supportive, online learning community of peers where ideas, experiences and learning resources can be shared. Addressing barriers to participation may enhance the learning experience of project ECHO in the future.